ANALYSIS OF CULTURAL MEANING, AND STRUCTURAL TYPOLOGY GREETINGS TO RESPECT THE VARIOUS MILITARY LANGUAGES OF THE TNI NAVY IN HISTORICAL PERSPECTIVE: ANALISIS MAKNA KULTURAL, DAN TIPOLOGI STRUKTURAL SAPAAN PENGHORMATAN RAGAM BAHASA MILITER TNI ANGKATAN LAUT DALAM PERSPEKTIF SEJARAH - Anwar Nada; Rustam Hasim (SOSIOEDUKASI, 2025)
This study aims to analyze the cultural meaning and structural typology of the salutation used in the various military languages of the Indonesian Navy, as well as to trace its historical development in the socio-cultural context of the Indonesian military. The military language of the Indonesian Navy has its own characteristics that reflect discipline, hierarchy, and honor values that are firmly rooted in the culture of military organizations. The method used is a qualitative descriptive method with a cultural, and historical linguistic approach. Data were obtained through observations, interviews, and studies of official documents and military archives. The results of the study show that the salutation in the military language of the TNI AL has a social and symbolic function that affirms identity, solidarity, and hierarchical structure between members. In terms of structural typology, it was found that there was a pattern of greetings that were systematically arranged based on rank, position, and the context of formal and informal communication. Meanwhile, culturally, each form of greeting contains basic values such as loyalty, respect for superiors, and corps spirit. From a historical perspective, the use of the greeting has evolved from the influence of colonial military traditions to the formation of a national identity that is typical of Indonesia. Thus, the greeting of respect in the military language of the TNI Navy is not only a form of verbal communication, but also a reflection of cultural values, military discipline, and historical heritage that shape the character of the TNI Navy institution to this day.